Pharmacology in anesthesia practice - Gupta, Anita; Singh-Radcliff, Nina (New York : Oxford University Press, 2013)
The grasp of pharmacologic principles and their practical application sits at the heart of anesthesiology practice. Intended to fill the niche for a rapid, point-of-care overview of clinical pharmacology in anesthesia, this compact guide covers the commonly prescribed medications in anesthesiology including the subspecialties of obstetric, regional, cardiac and neuroanesthesia.
Description based on print version record.
Keywords: Pharmacology; Anesthesiology; Anesthetics